1994
DOI: 10.1021/j100087a007
|View full text |Cite
|
Sign up to set email alerts
|

Proximity Effects on Nuclear Spin-Spin Coupling Constants. 1. J(CH) Couplings in the Vicinity of an Atom Bearing Lone Pairs

Abstract: Proximity effects on lJ(CH) couplings are studied from a theoretical point of view in the following systems:CH4/FH (A) and H*O/HCN (B) which form dimers by hydrogen-bond interactions. 'J(CH) couplings for different intermolecular distances are calculated for the C-H bond facing the atom bearing lone pairs. While in the former system, this coupling is increased owing to the proximity to the F atom; in the latter this coupling is decreased owing to the proximity to the 0 atom. These opposite trends are accompani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 5 publications
5
37
0
1
Order By: Relevance
“…Correlated results found in this work for 1 J(CH) in systems I and II complement previous findings [13,15] with new interesting qualitative features which are related to the expected behavior of the π- …”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Correlated results found in this work for 1 J(CH) in systems I and II complement previous findings [13,15] with new interesting qualitative features which are related to the expected behavior of the π- …”
Section: Discussionsupporting
confidence: 89%
“…couplings and C, H and O magnetic shielding constants [13,14,15]. In previous work, the change in J couplings was analyzed at the TDA [14] and CHF [13] levels since it was assumed that, even though it is well known that 1 J(CH) couplings are very sensitive to correlation effects, the changes in those couplings in the presence of the specific C-H...O interaction could probably be well reproduced at the uncorrelated level.…”
Section: J(ch)mentioning
confidence: 99%
“…For C(sp 3 )H and C(sp 2 )H bonds the electrostatic part of this proximate effect causes an increase in its corresponding 1 J(C,H) coupling [46][47] while the charge transfer contribution causes a decrease in such a coupling [2].…”
Section: Resultsmentioning
confidence: 99%
“…The sp 2 -hybridized C of the vinyl [41] or phenyl group [42][43][44][45] could also donate a proton, as could other aromatic systems such as imidazole [46], pyrimidine [47] or nucleic acid bases [48][49][50]. Other work concluded that the very simple CH 4 could engage in a HB [51][52][53][54][55][56][57][58][59][60][61], albeit a weak one. An early study of chlorosubstituted methanes [62] indicated that the CH··O HB with water would be progressively strengthened by each exchange of H with Cl.…”
Section: Early Calculationsmentioning
confidence: 99%